Pengaruh Profitabilitas, Solvabilitas, Ukuran Perusahaan dan Financial Distress Terhadap Audit Delay - Erika Cahya Gustiana; Dina Dwi Oktavia Rini (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine whether profitability, solvency, company size and financial distress have an effect on audit delay in Consumer Goods companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. This research method uses quantitative. The research population includes all consumer goods companies listed on the Indonesia Stock Exchange for the period 2016 – 2020, with a sampling technique using purposive sampling. The population in this study obtained data as many as 53 companies and obtained a sample of 19 companies. The analytical technique used is multiple linear regression analysis using SPSS version 26 test tool. The results of this study indicate that partially the profitability variable proxied by return on equity (ROE) has no effect on audit delay in consumer goods companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. While the solvency variable is proxied by debt to equity ratio (DER), company size as proxied by the natural logarithm of total assets and financial distress proxied by the Altman z-score has an effect on audit delay in consumer goods companies listed on the Indonesia Stock Exchange for the period 2016 – 2020.